Motherhood Studies and Feminist Theory: Elisions and Intersections - Takševa, Tatjana (Journal of the Motherhood Initiative for Research and Community Involvement, 2018)
The study of motherhood has had an uneasy and ambivalent relationship to feminism and feminist theory. Ranging from radical feminist rejection of motherhood on the perceived basis of its inherent oppression of women, and the view that “motherhood has everything to do with a history in which women remain powerless by reproducing the world of men” (Allen 316), to more moderate accounts of that ambivalence that caution against the “recent positive feminist focus on motherhood” that romanticizes motherhood by drawing heavily on sexist stereotypes (hooks 135), feminist thought continues to traverse with difficulty the complex terrain linking motherhood and maternal activity to feminist concerns. In this paper, I argue that there are complex intersections between feminist theory and motherhood studies that become particularly evident when motherhood is considered within a “third wave” context. By highlighting the development of motherhood studies within the context of third-wave feminism and its consistency with broad feminist ideals of female empowerment and social justice, I advocate for the systematic inclusion of the study of motherhood as a central aspect of women’s experience into established feminist, women, and gender studies agendas.